2004
DOI: 10.1038/nature02977
|View full text |Cite|
|
Sign up to set email alerts
|

The genome of Cryptosporidium hominis

Abstract: incubated with 20 ml Sepharose-immobilized monoclonal anti-HA antibodies (Covance). Beads were washed with buffer T without BSA before elution. DSP-induced crosslinks in eluted proteins were thiol-cleaved before separation by 8-16% SDS-PAGE and detection by Sypro Ruby (Bio-Rad). Quinone analysesLipid extractions and quinone detection were performed as described 19 . Hydrogenosomes (5.5 mg protein) were extracted and resuspended in 150 ml 9:1 methanol/ethanol, of which 50 ml was injected onto an HPLC system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
410
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(435 citation statements)
references
References 29 publications
14
410
0
5
Order By: Relevance
“…MQO is one of the few mitochondrial enzymes retained by Cryptosporidium spp. [9,65,66], suggesting that it may have a role in mitochondrial development or integrity. Moreover, MQO, together with FH, is one of only two TCA enzymes essential in the asexual stages of P. falciparum [36].…”
Section: Mitochondrial Metabolism Across the Alveolatamentioning
confidence: 99%
“…MQO is one of the few mitochondrial enzymes retained by Cryptosporidium spp. [9,65,66], suggesting that it may have a role in mitochondrial development or integrity. Moreover, MQO, together with FH, is one of only two TCA enzymes essential in the asexual stages of P. falciparum [36].…”
Section: Mitochondrial Metabolism Across the Alveolatamentioning
confidence: 99%
“…The complete genomes of six apicomplexans are currently available ( Fig. 2; Carlton et al 2002;Gardner et al 2002Gardner et al , 2005Abrahamsen et al 2004;Xu et al 2004;Pain et al 2005). Furthermore, large expressed sequence tag (EST) collections have been generated for an additional nine species (Ajioka et al 1998;Howe 2001;Li et al 2003a;Cui et al 2005), which can be used to construct so-called ''partial genomes '' (Peregrin-Alvarez and Parkinson 2007;Wasmuth et al 2008).…”
mentioning
confidence: 99%
“…Despite this, efforts to develop new and more effective treatments for this disease have been hindered by (1) lack of suitable targets and (2) lack of target validation and transfection tools. The completion of the Cryptosporidium genome (Abrahamsen et al, 2004;Xu et al, 2004), which resulted in a range of potential drug targets being identified, has overcome the first hindrance and IMPDH is now a well recognised and important drug target Johnson et al, 2013;Maurya et al, 2009;Sharling et al, 2010;Umejiego et al, 2008).…”
Section: Discussionmentioning
confidence: 99%